Smartphone Use and Academic Performance: Correlation or Causal Relationship? - Stijn Baert; Sunčica Vujić; Simon Amez; Matteo Claeskens; Thomas Daman; Arno Maeckelberghe; Eddy Omey; Lieven De Marez (Global Labor Organization (GLO), 2019)
After a decade of correlational research, this study attempts to measure the causal impact of (general) smartphone use on educational performance. To this end, we merge survey data on general smartphone use, exogenous predictors of this use, and other drivers of academic success with the exam scores of first-year students at two Belgian universities. The resulting data are analysed with instrumental variable estimation techniques. A one-standard-deviation increase in daily smartphone use yields a decrease in average exam scores of about one point (out of 20). When relying on ordinary least squares estimations, the magnitude of this effect is substantially underestimated. The negative association between smartphone use and exam results is more outspoken for students (i) with highly educated fathers, (ii) with divorced parents and (iii) who are in good health. Policy-makers should at least invest in information and awareness campaigns of teachers and parents to highlight this trade-off between smartphone use and academic performance.
Keywords: 330; smartphone use; academic performance; causality